A Gramscian Way to Understanding Populism - Mellino, Miguel (International Gramsci Journal, 2023)
This is the Abstract of the English-language version of the review by Miguel Mellino of the volume Gramsci e il populismo (ed. Guido Liguori), Milano, Unicopli, 2019, containing the proceedings of the 2018 International Gramsci Seminar on Gramsci and populism.